PENGARUH POLA ASUH ORANG TUA TERHADAP MINAT BERWIRAUSAHA DI SMK NEGERI 2 SINGKAWANG TENGAH - Ela Nura Kamaisel; Mashudi Mashudi; Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to find out "the effect of parenting parents on the interest in entrepreneurship of class XI students majoring in trade systems Smk Negeri 2 Singkawang Tengah". The method used was a quantitative descriptive method with a form of relationship research studies. Data collection techniques used were direct communication, indirect communication, direct observation, and documentary. Data collection tools used include questionnaires, interview guidelines, and documentation. The sample in the study showed that there was a positive effect of the influence of parenting on the interest in student entrepreneurship which indicated a correlation coefficient of 0.172. The coefficient of determination in this study shows the contribution of the influence of variables (X), namely the effect of parenting toward the dependent variable (Y), namely learning outcomes of 0.172 or 17.2%. While the rest are influenced by other variables not explained in this study. With a simple linear regression calculation, the equation Y = 1.875 + 0.722 X, which means a constant value of 1.875 if the influence of parenting is worth zero (0), then the interest in student entrepreneurship is 0.722, this means that an increase in learning readiness is 1 then learning outcomes will increase by 0.722. Keywords: Entrepreneurship in Interest, Parenting Parents